2018
DOI: 10.2147/ott.s153888
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-16 inhibited oral squamous carcinoma tumor growth in vitro and in vivo via suppressing Wnt/β-catenin signaling pathway

Abstract: BackgroundOral carcinoma, one of the most commonly diagnosed cancers, has a poor prognosis and low survival rate with treatment. In recent years, some studies reported the upregulation of miRNA-16 (miR-16) in the oral carcinoma, whereas some other studies confirmed the downregulation of miR-16. In the current study, we aimed to investigate the function of miR-16 in oral carcinoma.Materials and methodsCell proliferation assay was measured by MTT assay, quantitative real time polymerase chain reaction (qRT-PCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Upregulation of β-catenin expression in both MDA-miR-302/367 and SK-miR-302/367 cells by miR-16 inhibitor indicates an important role for miR-16 in regulation of β-catenin in the BC cells. Suppression of vimentin and β-catenin proteins by miR-16 has previously been reported in oral squamous cell carcinoma, 40 ovarian cancer cells, 41 chordoma cells, 42 and breast cancer cells by our group. 21 MiR-16 has been shown as an important suppressor of Wnt/β-catenin signaling pathway, 41 which targets WNT3A and Frizzled receptor gene, FZD6, as two important factors of β-catenin signaling cascade.…”
Section: Discussionsupporting
confidence: 73%
“…Upregulation of β-catenin expression in both MDA-miR-302/367 and SK-miR-302/367 cells by miR-16 inhibitor indicates an important role for miR-16 in regulation of β-catenin in the BC cells. Suppression of vimentin and β-catenin proteins by miR-16 has previously been reported in oral squamous cell carcinoma, 40 ovarian cancer cells, 41 chordoma cells, 42 and breast cancer cells by our group. 21 MiR-16 has been shown as an important suppressor of Wnt/β-catenin signaling pathway, 41 which targets WNT3A and Frizzled receptor gene, FZD6, as two important factors of β-catenin signaling cascade.…”
Section: Discussionsupporting
confidence: 73%
“…Watanabe et al (49) believed that the upregulation of HMGA2 expression activated the Ras signaling pathway, leading to the development of pancreatic cancer. The Wnt signaling pathway not only played a key role in regulating embryonic development, but also its abnormal activation was closely associated with the progression of tumors (50-53). Therefore, the present study ultimately indicated that the Wnt/β-catenin pathway was the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Wnt signaling/β-catenin pathway dysregulation is involved in cancer genesis, including oral cancer. This pathway is accompanied by various mechanisms, such as epithelial-mesenchymal transition and involvement of various miRNAs [ 51 , 52 ]. Participation of miR-30c-5p targets in this signaling pathway as shown by the pathway enrichment analysis underlies its role in oral cancer development.…”
Section: Discussionmentioning
confidence: 99%